The development and transfer of core competencies in multinational corporations : a study of three South African originated multinational corporations, compared and contrasted with a leading United States multinational - Harvey, Neil M (Rhodes University, Faculty of Commerce, Department of Management, 2007)
The thesis studies the development and transfer of core competencies in multinational corporations. It aims to advance the general body of knowledge relating to core competencies, to have practical applicability for management practitioners and academics, to explain how three companies from South Africa became global leaders in their fields and to examine the lessons they learned about international business. Three South African originated multinationals and a US multinational company were studied. The basic methodology is a case study. The methods of research were personal interviews, telephone interviews, written questionnaires, documents, archival records and direct observations. Value chains were used to evaluate the effectiveness of methods of development and transfer and the success of transfer of core competencies. It is concluded that different and multiple methods are needed to develop and transfer core competencies. The effectiveness of methods varies by company and value chain location. There is a significant high degree of correlation between the ratings of success in transferring core competencies and the effectiveness of the methods used to transfer them. This gives substantial credibility to the information provided by the companies and highlights the importance of selecting appropriate methods. There are some variances between the research results and established literature on the development and transfer of core competencies. There are notable differences between the companies from South Africa and the US multinational on the effectiveness of methods used to develop and transfer core competencies. There are also areas where all the companies are in accord. "Roadmaps" covering the effectiveness of methods for developing and transferring core competencies in different locations in a value chain are presented. Practical examples of the companies' actions relating to acquisitions and post-acquisition integration, their experiences in different countries, challenges they face, the methods used to assess transfer, avoid pitfalls and improve transfer, and other issues are also provided.The success of the multinationals from South Africa is explained by a combination of history, competitive factor conditions, management practices, attributes and leadership. The conclusions of the thesis are followed by recommendations on how to improve the management, development and transfer of core competencies.
Keywords: Management -- South Africa; International business enterprises -- South Afrca; International business enterprises -- United States; Core competencies